2021
DOI: 10.26434/chemrxiv-2021-n8lt5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemically Fueled Self-sorted Hydrogels

Abstract: Narcissistic self-sorting in supramolecular assemblies can help to construct materials with more complex hierarchies. Whereas controlled changes in pH or temperature have been used to this extent for two-component self-sorted gels, here we show that a chemically fueled approach can provide three-component materials with high precision. The latter materials have interesting mechanical properties, such as enhanced or suppressed stiffness, and intricate multi-step gelation kinetics. In addition, we show that we c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To create chemically fueled assemblies, we and others used a strategy in which a chemical reaction cycle transiently negates the charges on a molecule (Scheme 1D). [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Upon activation, an anionic, well-soluble precursor becomes charge-neutral, which induces product assembly. The deactivation occurs while the building block is assembled; it reinstates the negative charges and thus leads to its disassembly.…”
Section: Scheme 1 A) Scheme Of a Fuel-driven Reaction Cyclementioning
confidence: 99%
“…To create chemically fueled assemblies, we and others used a strategy in which a chemical reaction cycle transiently negates the charges on a molecule (Scheme 1D). [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Upon activation, an anionic, well-soluble precursor becomes charge-neutral, which induces product assembly. The deactivation occurs while the building block is assembled; it reinstates the negative charges and thus leads to its disassembly.…”
Section: Scheme 1 A) Scheme Of a Fuel-driven Reaction Cyclementioning
confidence: 99%
“…Dynamic light scattering (DLS) measurements demonstrated the presence of large assembled structures of aldehyde 1 even at [1]0 = 0.2 mM (Figure 4D). This suggests that the increase of [1]0 beyond 0.2 mM led to formation of more of assembled structures, while keeping the concentration of monomeric aldehyde nearly constant, because the self-assembly mechanism of this aldehyde is cooperative: 57 in the cooperative formation of supramolecular polymer, the concentration of a non-assembling monomer remains constant once the total monomer concentration exceeds the critical aggregation concentration. 58,59 Therefore, the increase of the catalysis rate at higher [1]0 is most likely the consequence of the increase in the amount of assembled structures, and we conclude that the catalysis of the fuel hydrolysis involves not only the monomeric aldehyde 1 but also their assemblies.…”
Section: Investigation Of the System's Mechanismmentioning
confidence: 99%
“…As such, at higher GdL concentrations the authors observed a fast gel−sol−gel conversion, whereas at lower GdL concentrations, the sol state was maintained for much longer. In more recent work, 105 the authors looked at three chemically similar gelators and showed that self-assembly into fibers can shield monomers from deactivation (by dithionite).…”
Section: Literature Examplesmentioning
confidence: 99%